The Role of Leadership in Public Sector Innovation: A Systematic Review and Meta-Analysis of the Management of COVID-19 in Asian Countries - Sazzad, Faizus; Rajan, V. Priya; Demircioglu, Mehmet Akif (Frontiers in Public Health, 2021)
Strong leadership in public sector innovation can empower governments to address community challenges in new ways in light of the challenges posed by the global coronavirus pandemic. Coronavirus management policy, pandemic responses, needs, and options are reflected in various Asian countries in respective published literature, but a summarized synthesis is not available. Using a systematic review approach (PRISMA), this study has analyzed the role of leadership in public sector innovation in COVID-19 management and synthesized 23 articles from 23 different Asian countries. In the light of available data, public sector innovation (PSI) and the role played by the leadership of each country’ have been found to be largely inter-dependent. The current review provides a cross-section of the ongoing nature of the pandemic, as management responses and trend data in the countries are still emerging or evolving. Additionally, our study contributes a current state report regarding the barriers facing the leadership of Asian countries in mitigating the global pandemic through PSI. Our study found that a strong political leadership presence combined with a technocratic approach and a highly-skilled public sector workforce, could lead to more tremendous success in managing the outbreak. Furthermore, religious leadership was also found to have a potentially significant role in COVID-19 management strategies.